Drying and rewetting foster phosphorus depletion of forest soils. (January 2019) - Brödlin, Dominik; Kaiser, Klaus; Kessler, Arnim; Hagedorn, Frank
Abstract: Phosphorus (P) is a key nutrient but still we have a limited knowledge on the controls of mobilization and fluxes of P in forest soils. Our study explored the linkages between P mobilization in organic horizons and mineral soils and the P status of soils, as affected by two consecutive drying and rewetting (D/W) cycles. We sampled litter layers (Oi), mixed Oe-Oa horizons, and A horizons in three beech forests along a P availability gradient in Germany. Carbon mineralization and release of dissolved organic matter (DOC, DOP) and dissolved inorganic P (DIP) were studied in microcosms exposed to an initial harsh drying (40 °C for 72 h) and a moderate dry spell (1 month at 20 °C). In Oi horizons, net P mineralization decreased with decreasing P status despite a similar C mineralization at all sites. This supports the general concept that the stoichiometric difference between substrate and microbial biomass primarily drives P release from decomposing organic matter. Counterintuitively, P mobilization per unit soil P increased towards P-poor sites in the mineral soil, likely due to decreasing contents of reactive secondary minerals and the consequently smaller P sorption. Drying and rewetting caused stronger mobilization of DIP and DOP (+108% on average) than of DOC (+51%). The parallel decline in specific UV absorptivity of DOM suggests that lysis of microbial cells drove the drought-induced P release. The D/W effects on P mobilization were particularly strong in P-poor soils, where greater portions of P are bound to microbial biomass, which are prone to become released upon rewetting. Since mobilized P can potentially be leached from soils, our findings indicate, that drought-induced P mobilization fosters the progressive P depletion of already P-poor soils. The possible P leaching losses from mineral soils seem rather be driven by soil mineralogy than by P status. Graphical abstract: Image 1 Highlights: Release of inorganic and organic P decreased with declining P contents in litter. In mineral soils, P release increased towards P-poor sites due to a smaller sorption. Contribution of organic as compared to inorganic P increased towards P-poor soils. Drying and rewetting caused a strong P mobilization, particularly in P-poor soils. Drought-induced P mobilization may foster the P depletion of already P-poor soils.